Effect of Incentive Spirometry on Recovery of Post-Operative Patients: Pre Experimental Study - Kaur, Akashdeep; Kalyani, C Vasantha; Kusum K (Universitas STRADA Indonesia, 2020)
Background: Post-operative care is management of patients after any surgery. The main goal of post-operative care is to prevent complications i.e. atelectasis and infection. The other objective is early healing of the surgical incision and return of patient to a state of health. About 17% to 88% of people in postoperative duration will have decreased lung volumes. This decreased lung volume problem can be solved with use of incentive spirometry in postoperative period on Day 1. Incentive spirometer is perioperative respiratory therapy given to postoperative patients to improve lung volume of patients and hasten recovery of patients also.Purpose: This study aimed to identify effect of Incentive spirometry on postoperative patient’s recovery.Methods: It was pre-experimental study with pretest- posttest design only, which was done on post-operative patients at All India Institute of Medical Sciences (AIIMS), Rishikesh.Results: Majority (52 %) of participants were 41 to 50 years age group. Male and female ratio for participants were 46:54. Paired ‘t’ test p value i.e. 0.00* with CI [0.72, 1.03] showed that on Pretest and Day 3 Performance level on incentive spirometry of participants showed a significant value, which indicate that spirometer enhance recovery of post-operative patients by increasing their lung volumes.Conclusions: This study revealed that incentive spirometry is effective in improving of pulmonary function among post-operative patients, which further improves blood circulation and hasten early recovery of surgical wound. This spirometry should be integral part of Post-operative care. All nurses who are involved in Postoperative units should encourage patients to do it on regular basis and document it as a vital sign. Good compliance to incentive spirometry can improve better outcome of patient’s